Improving The Ability To Read Poetry Texts Through The Discovery Learning Model In Students - Astuti, Dian; Sari, Esti Swatika (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to determine the improvement of the results of reading poetry text reading through the application  of the discovery learning  learning model in grade XI students of SMA Negeri 1 Sebuku and the improvement of the learning process of poetry texts by using  the discovery learning  model in students of grades XI-B SMA Negeri 1 Sebuku.This research is a class action research (PTK) that has been carried out at SMA Negeri 1 Sebuku Subjects in This class action study is class XI students of SMA Negeri 1 Sebuku, consisting of 27 people. The object of this study is the ability to read poetry texts through the application  of the discovery learning model. The research was carried out in two cycles consisting of four stages in each cycle, namely planning, implementation of actions, observation, and reflection. The data collection techniques used in this study include, observation, field notes, tests, and documentation. This study uses qualitative and quantitative data analysis techniques. The ability to read students' poetry texts is seen from the limit of achieving the minimum completeness criteria (KKM) which is 73 and is considered for the implementation of the next cycle. The results of the study show that the application of the discovery learning  model can improve the ability to read poetry texts in students in grades XI-B SMA Negeri 1 Sebuku. The improvement is shown by the quality of the learning process which is reflected in students' interest and attention to learning, students' enthusiasm for learning, student activeness, and students' punctuality in collecting assignments. The improvement in product terms can be seen from the average score of reading poetry texts from pre-action to cycle II. In the pre-action, an average score of 54.7% was obtained, then in the first cycle it increased to 67.4% and in the second cycle it increased significantly by 83.8%.